Determinants of Financial Risk Management in Micro, Small, and Medium Enterprises (MSMEs) in South Tangerang - Fahmi, Darul; Faisal, Rahman; Anthoni, Lukman (Jurnal Multidisiplin Sahombu, 2025)
This study explores the key determinants influencing financial risk management in micro, small, and medium enterprises located in South Tangerang. These enterprises play a crucial role in regional economic development but often face vulnerability due to limited resources and weak internal financial controls. The research examines the effects of financial governance, income tax management, business debt handling, and debt ratio on the effectiveness of financial risk management. Data were collected through a structured questionnaire and analyzed using the Structural Equation Modeling approach with Partial Least Squares. The findings reveal that financial governance and income tax management significantly enhance the quality of financial risk management practices. Conversely, the impact of business debt management and debt ratio was found to be statistically insignificant. These results suggest that strengthening financial administration and tax compliance is essential to mitigating financial risks. The study offers practical implications for policymakers, stakeholders, and MSME owners to develop more resilient financial strategies.